1989
DOI: 10.1021/jf00086a048
|View full text |Cite
|
Sign up to set email alerts
|

Studies on octylphenoxy surfactants. 7. Effects of Triton X-100 on sorption of 2-(1-naphthyl)acetic acid by tomato fruit cuticles

Abstract: The effects of a polyethoxy (EO) derivative of octylphenol (OP) with 9.5 ethyleneoxy groups (OP + 9.5EO) on 2-(l-naphthyl)acetic acid (NAA) sorption by cuticles enzymatically isolated from mature tomato (Lycopersicon esculentum Mill. cv. Sprinter) fruit were studied at pH 3.2 and 25 "C. Time to reach NAA sorption equilibrium by cuticular membranes (CM) or dewaxed CM (DCM) was not affected by OP + 9.5EO. At concentrations below the critical micelle concentration (CMC), OP + 9.5EO had little effect on NAA sorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…ex Hornem) leaves. The excised tissue was incubated in a mixture of cellulase (0.2% w/v, Sigma, St. Louis), pectinase (4% w/v, ICN Nutritional Biochemicals, Costa Mesa, Calif.), and NaN 3 (1 mM to prevent fungal and bacterial growth) in sodium citrate buffer (50 mM, pH 4.0) prepared in distilled water (Shafer and Bukovac, 1987;Yamada et al, 1964). Enzyme solution was changed several times over a 2week period.…”
Section: Methodsmentioning
confidence: 99%
“…ex Hornem) leaves. The excised tissue was incubated in a mixture of cellulase (0.2% w/v, Sigma, St. Louis), pectinase (4% w/v, ICN Nutritional Biochemicals, Costa Mesa, Calif.), and NaN 3 (1 mM to prevent fungal and bacterial growth) in sodium citrate buffer (50 mM, pH 4.0) prepared in distilled water (Shafer and Bukovac, 1987;Yamada et al, 1964). Enzyme solution was changed several times over a 2week period.…”
Section: Methodsmentioning
confidence: 99%
“…Wyrill and Burnside' reported that surfactants were more effective for glyphosate toxicity to common milkweed and hemp dogbane with increased ethoxylation. Gaskin and Holloway4 observed, with wheat and field bean, an optimum EO chain length (1 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for glyphosate uptake, as well as an influence of the hydrophobic moiety. Stevens and Bukovac" showed that the foliar uptake in maize of 2-deoxy-D-glucose, used as a model of a hydrophilic compound, was positively correlated with the hygroscopicity of octylphenoxy surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…4). 55 The sorption isotherm remains linear for 'Triton X-100' up to c. 1 glitre-'. Suppression of NAA sorption by cuticles in the presence of surfactant micelles can be attributed to solubilization of NAA in the m i c e l l e~.~~ UV spectroscopy confirms the presence of NAA molecules in the micelles at surfactant concentrations above the CMC.55,57,58 Micellar solubilization is greater when the NAA molecule is in the nondissociated form.58 These data show that micelles reduce the effective NAA concentration (driving force for sorption) in the sorbate solution and, thus, compete with the cuticle for the available NAA.…”
Section: Eflect Of Surfactant On Naa Sorptionmentioning
confidence: 92%
“…One can visualize curve C for a weak organic acid pesticide, where the pH is decreased, with reference to the pK,, resulting in a higher concentration of the more readily sorbed nondissociated species; and curve D, as the pH is increased above the pK,, yielding a higher concentration of the dissociated species.22* 4 4 9 7 2 Also, a response depicted by curve D may be obtained in the presence of a surfactant at a concentration above the CMC if the micelles of the surfactant solubilize the a.i. 55 Curve E suggests that the spray additive induced a change in the sorptive properties of the cuticle, thus delaying sorption equilibrium. Such changes may be caused by solubilizing and removing waxes, plasticizing or causing membrane swelling and, thus, increasing the mobility of the chain segments of the cutin polymer.…”
Section: Sorption As An Assay For Spray Additive Effectsmentioning
confidence: 99%
See 1 more Smart Citation